Evaluation of the Presentation of Operational Report in the Financial Sector Work Unit at the South Minahasa Resort Police - DOTULONG, Prisila M.; KALANGI, Lintje; KAPOJOS, Peter M. (Journal of Governance, Taxation and Auditing, 2023)
The operational report is a report that presents information on all financial operational activities reporting equity which is reflected in operating report income, operating surplus/deficit expenses of a reporting entity whose presentation is compared to the previous period so that the preparation of operational reports, reports of changes in equity, and balance sheets have a clear relationship can be accounted for. In practice, the presentation of operational presentation reports always refers to applicable regulations and uses applications that have been prepared and proven by documents and even accountability reports. This study aims to examine the presentation of operational reports on the Financial Sector Work Unit at the South Minahasa Polres. The results of the study show that The results study show that the presentation of operational reports in the Finance Sector Work Unit at the South Minahasa Polres has been carried out/implemented properly and is in accordance with applicable regulations, namely PMK RI Number 22/PMK.05/2022, this can be seen from the results of a comparison of the presentation of operational reports carried out by the Financial Sector Work Unit at the South Minahasa Polres based on Permendagri No.77 of 2020 is appropriate and well implemented.